Morphological changes in a macro-tidal estuary during extreme flooding events - Du, Yixiao; Cheng, Zhixin; You, Zaijin (Frontiers in Marine Science, 2023)
River discharge is a controlling factor in estuarine morphological changes; estuarine topography can be significantly altered even by only one flooding event. However, the mechanism of morphological changes in mountain-stream macro-tidal estuaries during wet seasons is not fully understood. Taking the Yalu River Estuary (YRE), China, as an example, this study aims to explore the effects of extreme flooding events on estuarine morphology. An improved Finite Volume Coastal Ocean Model (FVCOM) was applied in the YRE to reproduce the distribution of bed sediment erosion and deposition during dry years, normal years, and wet years. Sensitivity tests were conducted to assess the responses of the estuarine system to river discharge. The influence of the Yalu River on the magnitude of estuarine bed change was examined. With an increase in river discharge, the bed thickness in the main estuarine channel first increased and then decreased after reaching a threshold of 0.4 × 104m3/s. Simultaneously, density stratification became stronger with the increase in runoff. Subsequently, vertical mixing of water was weakened after a certain threshold, which in turn, enhanced the density stratification and changed the location of the Estuarine Turbidity Maxima (ETM). In addition, river effects contributed to nearly half of the bed erosion under 0.6 × 104m3/s (flooding with 50-year return period). The ETM extended and moved approximately 8 km seaward during flooding events. The West River channel experienced strong siltation, which was more significant during flood events. The results of this study demonstrate that estuarine circulation plays a key role in morphology change. The magnitude of bed thickness erosion can reach 22% of the total initial thickness during one flooding event. This rapid change is a threat to the stability of port infrastructures, and actions should be taken to maintain the safety of coastal construction.